Hybridization between char species (Salvelinus alpinus and Salvelinus fontinalis): a fast track for novel allometric trajectories - Dupont-Cyr, Bernard-Antonin; Dufresne, France; Christen, Félix; Desrosiers, Véronique; Proulx, Émilie; Le François, Nathalie R.; Vandenberg, Grant W.; Blier, Pierre Ulrich (Biology Open, 2018)
Hybridization between closely related species can generate genetic and phenotypic variation, providing valuable biological material to assess the physiological impact of the structural or functional variability of different organs. In the present study, we examined growth rates of various organs and whole body in brook char, Arctic char and their reciprocal hybrids over a period of 281 days. Parental species achieved significantly higher body mass than their hybrids. Hybridization significantly reduced the relative size of the heart, liver and spleen. The relative size of pyloric caeca did not differ among the four groups. The observed lower growth performance of the hybrids compared to parental species strongly suggests that divergence in the relative size of digestive organs, liver and heart partly dictate growth capacity. Our results also suggest that the increased variability achieved through hybridization may prove useful in a genetic selection program. -- Keywords : Arctic char Brook char Ontogeny Morphometry Heterosis Transgressive segregation.